Virtual Reality and Traveler Perception - Ma, Wenhui (International Journal of Social Sciences and Public Administration, 2024)
The emergence of virtual reality technology provides opportunities for rapid tourism growth. The highly realistic, immersive virtual reality experience offers a strong basis for travelers to understand tourism destinations better and shape travel intentions. This study aims to examine the positive impact of VR technology on tourism development and summarize the factors that influence travelers’ perceptions of VR to provide a theoretical basis for VR technology to provide high-quality services to travelers better.